2021
DOI: 10.1038/s41372-021-01066-x
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide mixed with surfactant did not affect neurodevelopmental outcomes at 6 or 18 months corrected age in observational cohorts

Abstract: Background The addition of budesonide to surfactant in very-low-birth-weight infants with less severe RDS decreased bronchopulmonary dysplasia (BPD) severity. Long-term neurodevelopmental follow-up was needed to monitor for systemic effects of budesonide. Methods Infants ≤1250 g who received intratracheal budesonide (0.25 mg/kg) with surfactant ( n = 173) were compared to a historical cohort who received surfactant alone ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 39 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…We found a decrease in the severity of BPD, as well as a decreased need for mechanical ventilation and postnatal corticosteroids [3]. These cohorts, similar to the Yeh study, also had no differences in motor or neurodevelopmental at 6 months or 18 months [17, 18]. To evaluate the acute effects on the HPA axis, we closely examined the physical and biochemical signs of adrenal insufficiency during the first 14 days in a 4-year cohort of ELBW infants exposed to budesonide.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…We found a decrease in the severity of BPD, as well as a decreased need for mechanical ventilation and postnatal corticosteroids [3]. These cohorts, similar to the Yeh study, also had no differences in motor or neurodevelopmental at 6 months or 18 months [17, 18]. To evaluate the acute effects on the HPA axis, we closely examined the physical and biochemical signs of adrenal insufficiency during the first 14 days in a 4-year cohort of ELBW infants exposed to budesonide.…”
Section: Introductionmentioning
confidence: 71%
“…The current cohort includes the initial 173 infants and an additional 141 infants exposed in the subsequent years [3,17]. Retrospective data collection on the infants up to discharge was extracted from the medical record with approval from the SLU Institutional Review Board (IRB#31767).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…65 And in the developmental follow-up of an observational study of infants exposed to intratracheal budesonide for the reduction of BPD, the infants who received budesonide had similar fine and gross motor skills at 4-6 months corrected age (CA), similar muscle tone on physician exams at 6 months CA, similar scores at 18-22 months CA on the Bayley III, these findings are similar to those of Yeh and Bassler et al Their studies confirmed that budesonide exposure did not affect nervous system development. 62,68,69 First of all, budesonide will be absorbed through the airways and it will rapidly dissolve into cellular lipids in the airways, there it will be rapidly and reversibly esterified by oleic and palmitic acids, and the budesonide esters have a low affinity for GR, thus no pharmacological effect will be exerted. 70,71 secondly, the systemic half-life of budesonide is much shorter than that of fluticasone propionate, the budesonide can be metabolized by members of the cytochrome P450 (CYP) 3A family of enzymes into a variety of inactive products in lung and liver microsomes, and finally cleaved to 16α-hydroxyprednisolone, thus the systemic exposure to budesonide can be minimized.…”
Section: The Advantages Of Budesonidementioning
confidence: 99%